Tayub Dance at Tambakromo Gunung Kidul Regency: An Ethnochoreological Perspective | Tari Tayub di Tambakromo Kabupaten Gunung Kidul: Dalam Perspektif Etnokoreologi - Pramutomo Mas; Sriyadi .. (SPAFA Journal, 2023)
Tayub is an old dance form in the Javanese cultural tradition. The value of Tayub’s ties to Javanese agrarian culture is associated with the form of village rituals. A village that still preserves the ritual of Village Purification is Tambakromo Village, Ponjong District in Gunung Kidul Regency, Yogyakarta. Tayub at Tambakromo Village is one of the rituals performed for extracting groundwater, referred to as Sendhang Milodo, in the Tukluk area. The traditional religiosity of Tambakromo Village believes in this sendhang as a source of life. This article describes the events of the Tayub dance performance in the Village Purification ritual during the Covid-19 pandemic era using an ethnochoreological approach. In the era of the Covid-19 pandemic, the people of Tukluk Sub-Village, Tambakromo Village, continued to carry out the Village Purification ritual by performing the Tayub dance. Government regulations regarding the use of masks and keeping a safe distance are not obstacles in performing the Tayub dance, even though this dance is a social dance. The community continues to carry out the Village Purification ritual according to the traditional calendar that has been passed down from generation to generation. There is even a belief that the Village Purification ritual is a magical protection which if not carried out will bring disaster to the local community.